Perbandingan Hasil Belajar Siswa Melalui Strategi Pembelajaran Joyful Learning Dan Everyone Is A Teacher Here Kelas X Teknik Sepeda Motor (TSM) Dan Kelas X Teknik Gambar Bangunan (TGB) Pada Materi Termodinamika - Dewi, Sulasteri; Rafiqah, Rafiqah; Suhardiman, Suhardiman (Al-Khazini: Jurnal Pendidikan Fisika, 2021)
The purpose of this study is to: compare learning outcomes between students who  are  taught  the  Joyful  Learning  strategy  with  the  Every  One  is  A Teacher Here strategy on thermodynamics class X SMKN 1 South Sulawesi. This  type  of  research  is  classified  as  pre-experimental  using  a  comparative study  research  approach,  learning  outcomes  after  being  taught  using  the Joyful  Learning  learning  strategy  with  the  Every  One  is  A  Teacher  Here learning strategy for students in class X TSM and class X TGB. The results showed that the class taught using the Joyful  Learning  learning strategy the average  value of the  students was  in the good predicate category (B+), and the class taught using the Every One is A Teacher Here learning strategy the average  student  score  was  in  the  good  category  (B).  It  was  concluded  that there was a difference  between the classes taught using the Joyful  Learning learning strategy with higher learning outcomes than the classes taught using the Every One is A Teacher Here learning strategy.The implications of this research are: In learning physics to get high participation from each student, as an option, you can use the Every One Is a Teacher Here learning strategy, and  to  make  students  not  feel  pressured,  they  can  use  the  Joyful  Learning learningstrategy as an option.